Il Nunavut dalla pagina allo schermo: la traduzione audiovisiva di The Snow Walker di Farley Mowat - Sasso, Eleonora (Ledizioni, 2022)
This essay takes as its starting points the notion of remediation and the linguistics of subtitling in order to advance a new reading of the audiovisual translation of Farley Mowat’s short story Walk Well, My Brother (1975), whose remediation in film The Snow Walker (2003) is a paramount example of foreignising translation aimed at protecting the ethno-cultural diversity in Canada. Not only such an Inuit film with subtitles as The Snow Walker envisions the clash between Canadian and Inuit cultures but is also a survival tale in the far North examining the relationship between technology and minority cultures. I track through these references and look at the issues – the role of subtitling in the preservation of cultural specificity, subtitling strategies for rendering culture-bound terms, cohesion and coherence in subtitling, segmentation, etc. – which they raise. But my central purpose is to re-read the aforementioned subtitled film by applying the linguistics of subtitling and its text-reduction shifts. I analyse the problems of rendering intra-linguistic and extra-linguistic cultural elements from one language and cultural into another in order to demonstrate the challenge of rendering hybrid forms or multilingualism. Through The Snow Walker, I suggest, subtitling may be considered as an extreme form of foreignisation, a modality which is able to conceptualise cultural diversity thereby avoiding ethnocentric violence.